Patterns of indigenous female cattle morphometric traits variations in Uganda: Evidence for farmers’ selection to enhance agro-ecological fitness - Kabi, Fredrick; Masembe, Charles; Negrini, Riccardo; Muwanika, Vincent B. (Animal Genetic Resources, 2015)
Globally, rural cattle keeping communities actively select and breed indigenous cattle to satisfy their interests and enhance adaptation to local landscapes. This study investigated how traditional systems in Uganda have shaped the morphometric population structure of indigenous cattle breeds. Ten linear morphometric traits were interrogated amongst 801 female cattle, comprising 46 Nganda (Bos indicus), 368 Ankole (B. taurus indicus) and 387 East African shorthorn zebu (EASZ, B. indicus). The study cattle were obtained evenly at random from 209 herds in their agro-ecological zones (AEZs) where they have been nurtured by traditional cattle keeping communities throughout Uganda. Age, AEZs and breed significantly influenced the variation of linear morphometric traits exhibiting a gradient of low, intermediate and high dimensions among the EASZ, Nganda and Ankole cattle, respectively. Likewise, the linear morphometric trait (Mahalanobis squared distance) diversity was significantly different exhibiting a gradient of low, intermediate and high variation between Nganda and EASZ, Ankole and Nganda, and Ankole and EASZ cattle, respectively. These findings demonstrate the role of agro-ecological fitness in the evolution of indigenous cattle morphometric population structure in Uganda. The study outcomes further provide a motivation to search for genes associated with the diverse morphometric features
Keywords: adaptation; agro-ecological fitness; female indigenous cattle; linear morphometric trait variation; Uganda